Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$$ \begin{align*} &= (n+1)! − 1 + ( (n+1) · (n+1)! )\\ &= (n+1)! (1+n+1) − 1\\ &= (n+1)! (n+2) − 1\\ &= (n+2)! − 1\\ \end{align*} $$

I'm confused at how the first step goes to the second step. Can someone please clarify this?

share|improve this question

1 Answer 1

up vote 5 down vote accepted

It's just the distributive law $\rm\ k!\ (1 + k)\ =\ k! + k\ k!\ $ for $\rm\ k = n+1.$

TIP $\ $ Often applications of simple laws are obfuscated in specific proofs. In such contexts, in order to abstract out the essential structure, it may help to substitute variables for expressions that play no role. Let's do this above. Substituting $\rm (n+1)!\ \to\ x,\ \ n+1\ \to\ y\ $ the first two steps become

$$\rm x - 1 + y\ x\ = \ x\ (1 + y) - 1 $$

which makes obvious the application of the distributive law.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.